Recurrence risk of venous thromboembolism and hormone use in women from England: a cohort study using clinical practice research datalink - Kiconco, Sylvia; Abdul Sultan, Alyshah; Grainge, Matthew J. (Wiley, 2017)
It is vital to identify people with low recurrence risk of venous thromboembolism (VTE) so as to protect them from dangers of prolonged anticoagulation therapy. Among women who develop VTE following hormone use, the evidence as to whether their risk of recurrence is low if they cease this therapy is conflicting. We investigated whether women whose initial VTE event was hormone-related have a lower risk of VTE recurrence than women whose initial event had no obvious cause (unprovoked). A cohort study utilising the Clinical Practice Research Datalink linked to Hospital Episode Statistics data from England was conducted. We selected 4170 women aged between 15 and 64 years who were diagnosed with a first VTE event between 1997 and 2011. Cox regression models were used to obtain hazard ratios (HR). Hormone users had 29% lower recurrence risk than non-users (adjusted HR = 0·71; 95% confidence interval 0·58–0·88), a relationship which existed both in women aged 15–44 years (predominantly oral contraceptive users) and those aged 45–64 years (predominantly hormone replacement therapy users). In conclusion, having a hormone-associated VTE is associated with a lower recurrence risk than one that is unprovoked after discontinuation of the hormone-containing preparation. Prolonged anticoagulation may therefore be unjustified in such women.